Thermal decomposition kinetics of sugarcane mills wastes - da Silva, Daniel R. [UNESP]; Crespi, Marisa S. [UNESP]; Ribeiro, Clóvis A. [UNESP]; Capela, Jorge M. V. [UNESP] (Springer Nature, 2018)
The aim of this work was to evaluate the kinetic parameters regarding the first thermal decomposition mass loss step of organic matter present in samples of bagasse, filter cake, and vinasse provided by two sugarcane mills by TG in pyrolysis and combustion conditions. LL-INT Wanjun–Donghua procedure modified by Capela–Ribeiro was employed to estimate activation energy in function of the extent of conversion. The chemical composition of samples was determined by ultimate analysis, FTIR spectroscopy, X-ray diffractometry, and atomic absorption spectrophotometry among other analytical techniques. Results indicated that despite similar organic composition, the energetic potential of filter cake and vinasse was lower than that of bagasse due to their increased inorganic content. Filter cake presented high amounts of Ca, Cu, Fe, Mn, P, and Zn. Vinasse showed greater concentrations of Na and K and higher amounts of other metals such as Ca, Mg, Mn and Zn than bagasse and filter cake samples. Filter cake and vinasse samples had significant concentrations of heavy metals like Cr and Pb. However, considerable differences were observed when the chemical composition of samples from a same type of waste was compared. Different kinetic mechanisms of reaction were observed for a same kind of waste which resulted in variation of mean activation energy values. Regarding this parameter, samples that were subjected to nucleation presented lower values than the ones that showed geometrical contraction. The order-based models were responsible for the elevation of activation energy. Despite these facts, the kinetic compensation effect was observed for all samples in both pyrolysis and combustion atmospheres.
Keywords: Bagasse; Filter cake; Sugarcane; Thermal decomposition kinetics; Vinasse